L'emploi du citrate de triammonium pour le nettoyage des couches picturales contemporaines - Caroline Dupré (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Triammonium citrate has been employed for surface cleaning of varnished or unvarnished paintings. What risks for original materials are connected with the application of TAC solution ? The observation of the behavior of large samples of artists’colours exposed to solutions of TAC has allowed to examine the influence of various concentrations on the materials.